High-transparency polyethylene heat shrink film and preparation method thereof
By adopting a combination of multi-layer structure and specific materials, the problem of insufficient transparency and toughness of polyethylene heat shrink film is solved, and high transparency and excellent mechanical properties are achieved, while enhancing the resistance to UV.
Patent Information
- Application Number
- CN202411761421.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-11
AI Technical Summary
The existing polyethylene heat shrink films have shortcomings in terms of transparency and toughness, which are poor in transparency and are prone to brittleness.
A highly transparent polyethylene heat shrink film with a multi-layer structure, including the outer layer, the sub-outer layer, the middle layer and the outer layer, is prepared by melting, extrusion, blowing and corona processes such as cellulose nanofibers, tannin acid, modified nanosilica sol and epoxy resin to improve transparency and UV resistance.
It significantly improves the transparency and mechanical properties of the heat-shrinkable film, reduces the film thickness, enhances the tensile, puncture and tear resistance, and improves the resistance to UV aging.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging films, and more specifically, to a highly transparent polyethylene heat shrinkable film and a preparation method thereof. Background Art
[0002] Due to its excellent physical and mechanical properties such as shrinkage, tensile strength and breaking strength, heat shrinkable film can package and protect items to achieve the functions of dust-proof, moisture-proof and oil-proof. In addition, PE heat shrinkable film is light in weight, low in cost, recyclable and has good protective effect. It is sought after by companies in the fast-moving consumer goods industry such as beer, mineral water and beverages, and is widely used in the bundled packaging and transportation of products such as cans, glass bottles and plastic bottles.
[0003] At present, most polyethylene heat shrink films on the market are processed and produced using low-density polyethylene alone or a blend of high-density polyethylene and low-density polyethylene. Although the heat shrink film has high shrinkage and mechanical properties, the film products are relatively thick, usually above 100μm, and the transparency is poor, which affects the appearance of the goods after packaging. With the development of heat shrink film processing technology, thinning and transparency enhancement of heat shrink film have become new development trends. Medium-density metallocene polyethylene has gradually become one of the main raw materials for processing heat shrink film. With the addition of metallocene polyethylene resin, the mechanical properties of the heat shrink film are further improved, the thickness of the film is reduced, and the transparency of the film is improved. However, the existing heat shrinkable film, although it has high heat shrinkage in one direction, has too low toughness and is prone to becoming brittle in the other direction. Therefore, it is of great importance to further improve the toughness of polyethylene heat shrink film. Summary of the invention
[0004] In order to improve the transparency of a polyethylene heat shrinkable film and improve the toughness of the heat shrinkable film, the present application provides a highly transparent polyethylene heat shrinkable film and a preparation method thereof.
[0005] In a first aspect, the present application provides a highly transparent polyethylene heat shrinkable film, which adopts the following technical solution: A highly transparent polyethylene heat shrinkable film, comprising an outer layer, a sub-outer layer, a middle layer, a sub-outer layer and an outer layer arranged in sequence; The outer layer includes No. I MLLDPE, the sub-outer layer includes No. II MLLDPE, and the inner layer includes LDPE, No. II MLLDPE and HDPE in a mass ratio of 1:1-1.4:1-1.2; The density of the No. 1 MLLDPE is 0.925-0.927 g / cm 3 , melt index is 1.3-1.5g / 10min; The density of the II MMLDPE is 0.9-0.92 g / cm 3 , the melt index is 0.5-1g / 10min.
[0006] By adopting the above technical scheme, No. II MLLDPE is used in the middle layer and the sub-outer layer, and HDPE and LDPE are used in the middle layer. MLLDPE is also called metallocene. MLLDPE has outstanding tensile properties, impact strength and puncture resistance. These properties can make the product thin-walled and thinnable, and can reduce the thickness of the heat shrink film while improving the tensile strength, puncture resistance and tear resistance of the heat shrink film. LDPE has the advantages of high strength, good toughness, heat resistance and cold resistance. It also has good environmental stress cracking resistance, impact strength and tear strength resistance. Under the thinning effect of No. II MLLDPE, the tensile performance of the heat shrink film can be increased, while HDPE has excellent deformation resistance, can maintain the stability and integrity of the film, and improve the maximum tensile force and friction that the heat shrink film can withstand; No. I MLLDPE in the outer layer is Exceed 1327KD, which is a metallocene Ethylene-ethane copolymer can obtain a film with high modulus and good toughness, and its formula contains lubricants and opening agents, making it a general polymer that can be used immediately for forming, filling and sealing. The opening agent addition amount is 750ppm, and the lubricant addition amount is 1300ppm. The opening agent contained can increase the fluidity of the product, reduce the friction coefficient, improve the production efficiency of the finished product, reduce the friction between the film materials, and make the film materials easier to unfold and shrink. The lubricant can reduce the apparent viscosity and extrusion temperature of the outer layer, making the film materials easier to flow and form during the processing process. It can also eliminate melt fracture and die accumulation, reduce cross-linked gel and oxidized gel during extrusion, improve product quality, and improve the surface gloss of the film material. Therefore, the heat shrinkable film produced has good heat shrinkage and mechanical properties, not only good transparency, but also the film material thickness is reduced by more than 50%, which can effectively reduce the company's raw material consumption.
[0007] Optionally, the mass ratio of the outer layer No. I MLLDPE, the sub-outer layer No. II MLLDPE and the middle layer No. II MLLDPE is 2-2.5:2-2.5:1.
[0008] By adopting the above technical solution, outer layer No. I MLLDPE, sub-outer layer No. II MLLDPE and middle layer No. II MLLDPE are used as raw materials according to the above dosage ratio, so as to obtain a heat shrinkable film with better transparency and higher mechanical strength.
[0009] Optionally, 3-5 parts by weight of ultraviolet protection agent are also added to the outer layer.
[0010] By adopting the above technical solution, the heat shrink film will age when exposed to sunlight for a long time under the action of ultraviolet rays, thereby affecting the mechanical strength and light transmittance of the heat shrink film. Therefore, using an appropriate amount of ultraviolet protective agent in the outer layer can enhance the ultraviolet protection effect of the heat shrink film and reduce the occurrence of mechanical strength loss and transparency deterioration caused by aging of the heat shrink film after ultraviolet irradiation.
[0011] Optionally, the preparation method of the ultraviolet protection agent is as follows: The cellulose nanofibrils are placed in deionized water and ultrasonically dispersed for 1-2 hours to obtain a suspension with a concentration of 0.5-1 wt%, which is then filtered to obtain a cellulose membrane; The cellulose membrane is vacuum impregnated in a mixed solution containing modified nano-silica sol and tannic acid, and then dried at 45-50° C. for 10-12 hours to obtain a modified cellulose membrane, wherein the mass ratio of tannic acid to modified nano-silica sol is 0.7:15-16; The epoxy resin and the curing agent are mixed to prepare the epoxy resin emulsion, the modified cellulose film is immersed in the epoxy resin emulsion for 10-20 minutes, pressed at a pressure of 0.03-0.035 MPa until the epoxy resin is completely cured, and crushed to prepare the ultraviolet protective agent.
[0012] By adopting the above technical scheme, cellulose nanofibrils have certain gas barrier properties and can improve the UV resistance of heat shrinkable film to a certain extent. They are dispersed in deionized water and filtered to obtain a cellulose film with a fiber network structure. However, there are a large number of gaps between the fibers, which will cause light scattering and affect transparency. Therefore, vacuum impregnation is performed using a sol containing tannic acid and modified nano-silica. Tannic acid has high-density hydrogen bonding sites and excellent UV absorption properties, and can form strong hydrogen bonds with cellulose nanofibrils, giving cellulose nanofibrils UV resistance. Modified nano-silica has a low specific surface energy, transparency and hydrophobicity. , and fills the network structure composed of cellulose nanofibrils to reduce light scattering and improve light transmittance. In addition, silica can significantly improve the weather resistance of heat shrinkable film by preventing ultraviolet damage and inhibiting oxidation reactions, and reduce ultraviolet damage caused by long-term exposure. Modified nano-silica sol can increase the adhesion of tannic acid on the surface of cellulose film and improve anti-ultraviolet durability, but the surface is relatively rough at this time. Epoxy resin is deposited on the surface of modified cellulose film. Modified nano-silica sol gives modified cellulose film hydrophobicity, making epoxy resin deposited more evenly on its surface, making the structure of modified cellulose film denser and smoother, so as to have better transparency.
[0013] Optionally, the modified nano-silica sol is prepared by the following method: dispersing nano-silica in a polyvinyl alcohol aqueous solution with a concentration of 8-10wt%, ultrasonicating for 20-30min, adding water-soluble carbon quantum dots and divinyltetramethyldisilazane, and mixing evenly to prepare the modified nano-silica sol, wherein the mass ratio of silica, divinyltetramethyldisilazane and water-soluble carbon quantum dots is 1:0.6-0.9:0.2-0.4.
[0014] By adopting the above technical scheme, nano silicon dioxide is dispersed in the polyvinyl alcohol aqueous solution. During vacuum impregnation, polyvinyl alcohol can penetrate well into the pores of the cellulose membrane and fuse well with the carbon quantum dots to encapsulate them in the cellulose membrane and form a dense structure, which is helpful to inhibit light scattering and improve transmittance. As an ultraviolet light conversion medium, the carbon quantum dots can emit visible light under ultraviolet light excitation, thereby resisting ultraviolet light penetration and improving the anti-ultraviolet ability. Moreover, the silazane hydrolysis-stable group CH2=CH-Si-(CH3)2 in divinyltetramethyldisilazane reacts with the hydroxyl groups in the nano silicon dioxide and polyvinyl alcohol to replace the hydrophilic group hydroxyl groups in the sol with hydrophobic groups. Moreover, the steric hindrance of the CH2=CH-Si-(CH3)2 group is large and the reaction activity is poor, so that the nano silicon dioxide ions are agglomerated smaller and the dispersion is better, thereby improving the dispersion of the nano silicon dioxide, reducing its agglomeration, making it more evenly distributed when impregnated on the surface of the cellulose membrane, reducing the influence of its agglomeration on transparency, and increasing the anti-ultraviolet aging ability.
[0015] Optionally, the vacuum degree of the vacuum impregnation is 0.05-0.08 MPa, and the impregnation time is 40-60 min.
[0016] By adopting the above technical solution, the above vacuum degree and time can make the modified nano-silica sol and tannic acid fully impregnated and filled into the pores of the cellulose membrane, so that the cellulose membrane has low porosity, high transparency and stronger UV resistance.
[0017] Optionally, the thickness ratio of the outer layer, the sub-outer layer, the middle layer, the sub-outer layer and the outer layer is 1:2-3:6:2-3:1.
[0018] By adopting the above technical solution, the heat shrinkable film with the above thickness can maintain excellent light transmittance and has strong tensile and tear resistance.
[0019] Optionally, in the middle layer, the density of LDPE is 0.921-0.922 g / cm 3 The melt index is 0.33-0.4 g / 10 min, and the density of the HDPE is 0.949-0.961 g / cm 3, the melt index is 0.7-0.82g / 10min.
[0020] By adopting the above technical scheme, LDPE and HDPE with the above density and melt index have excellent toughness and outstanding optical properties, which can provide an excellent balance between processing and film properties for different resins, including stretchability, impact resistance and puncture resistance, and have a significant toughness improvement effect.
[0021] In a second aspect, the present application provides a method for preparing a highly transparent polyethylene heat shrinkable film, using the following technical solution: A method for preparing a highly transparent polyethylene heat shrinkable film comprises the following steps: No. I MLLDPE is used as the outer layer material, No. II MLLDPE is used as the secondary outer layer material, and LDPE, No. II MLLDPE and HDPE are mixed as the middle layer material; The outer layer raw material, the sub-outer layer raw material and the middle layer raw material are melted, extruded and inflated to obtain film bubbles, which are then pulled and corona-treated to obtain a polyethylene heat shrinkable film.
[0022] By adopting the above technical scheme, various raw materials of the outer layer, the sub-outer layer and the middle layer are first mixed and granulated, so that the raw materials of each layer can be fully mixed, and the uniformity and stability of the raw materials of the outer layer, the sub-outer layer and the middle layer can be improved.
[0023] Optionally, the blowing ratio is 1.2-3, the drawing ratio is 5-7, the melting temperature of the outer layer is 140-150°C, the melting temperature of the sub-outer layer is 150-180°C, and the melting temperature of the middle layer is 170-190°C.
[0024] In summary, this application has the following beneficial effects: 1. Since the present application uses MLLPDE with different densities and melt indexes as the raw materials for the outer layer and the sub-outer layer, and uses the same MLLDPE as the sub-outer layer in the middle layer, the thickness of the heat shrinkable film is effectively reduced, its transparency is improved, and the tensile strength and puncture strength of the heat shrinkable film are increased.
[0025] 2. In the present application, cellulose nanofibrils, tannic acid, modified nano-silica sol and epoxy resin are preferably used to prepare the UV protective agent. The cellulose nanofibrils are used to form a network structure, and then tannic acid and modified nano-silica are vacuum impregnated to fill the network pores, reduce light scattering, improve transparency, and increase UV resistance. Finally, epoxy resin is used to increase the hydrophobicity, transparency and UV resistance of the cellulose nanofibril matrix, improve the dispersion uniformity of the UV protective agent in the outer layer, and increase the UV resistance and transparency of the heat shrinkable film.
[0026] 3. In the present application, it is preferred to prepare the modified nano-silica sol by mixing nano-silica, polyvinyl alcohol aqueous solution, carbon quantum dots and divinyltetramethyldisilazane. Polyvinyl alcohol can increase the permeability of nano-silica and carbon quantum dots on the cellulose membrane, reduce the porosity, and increase the transparency. Carbon quantum dots can increase the UV resistance. Divinyltetramethyldisilazane can improve the hydrophobicity, increase the dispersibility of silica, and reduce agglomeration. DETAILED DESCRIPTION
[0027] The following examples further illustrate the present application in detail.
[0028] Preparation Example 1-10 of UV Protective Agent
[0029] In Preparation Example 1, the cellulose nanofibrils are selected from Nanjing Tianlu Nanotechnology Co., Ltd., with a diameter of 3-5 nm and a length of 500-1000 nm. The epoxy resin is selected from Wuxi Qianguang Chemical Raw Materials, with a brand name of E-44 and a model number of WSR6101.
[0030] Preparation Example 1: Cellulose nanofibrils were placed in deionized water and ultrasonically dispersed at a power of 250 W for 2 h to obtain a suspension with a concentration of 1 wt%, which was then filtered to obtain a cellulose membrane; The cellulose membrane was vacuum impregnated in a mixed solution containing nano-silica sol and tannic acid, and then dried at 45°C for 12 hours to obtain a modified cellulose membrane. The mass ratio of tannic acid to nano-silica sol was 0.7:16, the vacuum degree during vacuum impregnation was 0.08 MPa, the impregnation time was 40 minutes, the concentration of silica sol was 30 wt%, and it was made by mixing 30 g of nano-silica and deionized water. 100g of epoxy resin and 33g of curing agent diethylenetriamine were mixed to prepare epoxy resin emulsion, and the modified cellulose film was immersed in the epoxy resin emulsion for 20 minutes, pressed at a pressure of 0.035MPa until the epoxy resin was completely cured, and crushed to 0.3mm to prepare a UV protective agent.
[0031] Preparation Example 2: Cellulose nanofibrils were placed in deionized water and ultrasonically dispersed at a power of 300 W for 1 h to obtain a suspension with a concentration of 0.5 wt%, which was then filtered to obtain a cellulose membrane; The cellulose membrane was vacuum impregnated in a mixed solution containing 100g of nano-silica sol and tannic acid, and then dried at 50°C for 10h to obtain a modified cellulose membrane, wherein the mass ratio of tannic acid to nano-silica sol was 0.7:15, the vacuum degree during vacuum impregnation was 0.05MPa, the impregnation time was 60min, the concentration of silica sol was 30wt%, and the membrane was prepared by mixing 30g of nano-silica and deionized water; 100g of epoxy resin and 33g of curing agent diethylenetriamine were mixed to prepare epoxy resin emulsion, and the modified cellulose film was immersed in the epoxy resin emulsion for 10 minutes, pressed at a pressure of 0.03MPa until the epoxy resin was completely cured, and crushed to 0.3mm to prepare a UV protective agent.
[0032] Preparation Example 3: The difference from Preparation Example 1 is that silica sol is not used.
[0033] Preparation Example 4: Cellulose nanofibrils were placed in deionized water and ultrasonically dispersed at a power of 250 W for 2 h to obtain a suspension with a concentration of 1 wt%, which was then filtered to obtain a cellulose membrane; 100g of epoxy resin and 33g of curing agent diethylenetriamine were mixed to prepare epoxy resin emulsion. The cellulose film was immersed in the epoxy resin emulsion for 20 minutes, pressed at a pressure of 0.035MPa until the epoxy resin was completely cured, and crushed to 0.3mm to prepare a UV protective agent.
[0034] Preparation Example 5: Cellulose nanofibrils were placed in deionized water and ultrasonically dispersed at a power of 250 W for 2 h to obtain a suspension with a concentration of 1 wt%, which was then filtered to obtain a cellulose membrane; The cellulose film was vacuum impregnated in a mixed solution containing nano-silica sol and tannic acid, dried at 45°C for 12 hours, and crushed to 0.3 mm to obtain a UV protective agent. The mass ratio of tannic acid to nano-silica sol was 0.7:16, the vacuum degree during vacuum impregnation was 0.08 MPa, the impregnation time was 40 minutes, the silica sol concentration was 30wt%, and it was made by mixing 30g of nano-silica and deionized water.
[0035] Preparation Example 6: The difference from Preparation Example 1 is that the nano-silica sol is a modified nano-silica sol, and the preparation method of the modified nano-silica sol is as follows: 30g of nano-silica was dispersed in 70g of 10wt% polyvinyl alcohol aqueous solution, and ultrasonicated at 300W power for 30min, and water-soluble carbon quantum dots and divinyltetramethyldisilazane were added and mixed evenly to prepare modified nano-silica sol, the mass ratio of silica, divinyltetramethyldisilazane and water-soluble carbon quantum dots was 1:0.9:0.4, the alcoholysis degree of polyvinyl alcohol was 99%, and the relative molecular mass was 440,500.
[0036] Preparation Example 7: The difference from Preparation Example 1 is that the nano-silica sol is a modified nano-silica sol, and the preparation method of the modified nano-silica sol is as follows: 30g of nano-silica was dispersed in 70g of 8wt% polyvinyl alcohol aqueous solution, and ultrasonicated at 300W power for 20min, and water-soluble carbon quantum dots and divinyltetramethyldisilazane were added and mixed evenly to prepare modified nano-silica sol, the mass ratio of silica, divinyltetramethyldisilazane and water-soluble carbon quantum dots was 1:0.6:0.2, the alcoholysis degree of polyvinyl alcohol was 99%, and the relative molecular mass was 440,500.
[0037] Preparation Example 8: The difference from Preparation Example 6 is that no water-soluble carbon quantum dots are added.
[0038] Preparation Example 9: The difference from Preparation Example 6 is that divinyltetramethyldisilazane is not added.
[0039] Preparation Example 10: The difference from Preparation Example 6 is that an equal amount of deionized water is used instead of the polyvinyl alcohol aqueous solution. Example
[0040] Example 1: A highly transparent polyethylene heat shrinkable film, comprising an outer layer, a sub-outer layer, a middle layer, a sub-outer layer and an outer layer laminated in sequence with a thickness ratio of 1:3:6:3:1. The amount of raw materials used in each layer is shown in Table 1. The melt index (190°C, 2.16kg) of the outer layer No. I MLLDPE in Table 1 is 1.3g / 10min, and the density is 0.927g / cm 3 , selected from Exceed 1327KD, the melt index (190℃, 2.16kg) of the MLLDPE of the second outer layer and the inner layer II is 0.5g / 10min, and the density is 0.92g / cm 3 , selected from ExxonMobil, the grade is 4002HH, the density of LDPE in the inner layer is 0.922g / cm 3 , melt index (190℃, 2.16kg) is 0.33g / 10min, selected from ExxonMobil, model LD165BW1, HDPE density is 0.961g / cm 3 , the melt index (190°C, 2.16kg) is 0.7g / 10min, selected from ExxonMobil, model HTA-108.
[0041] The method for preparing the above-mentioned highly transparent polyethylene heat shrinkable film comprises the following steps: S1. According to the amounts in Table 1, No. I MLLDPE is used as the outer layer raw material, No. II MLLDPE is used as the secondary outer layer raw material, and LDPE, No. II MLLDPE and HDPE are mixed as the middle layer raw material; S2. The outer layer raw material, the sub-outer layer raw material and the middle layer raw material are melted, extruded and blown to obtain film bubbles, which are then pulled and corona treated to obtain a polyethylene heat shrinkable film. The blowing ratio is 3, the pulling ratio is 7, the outer layer melting temperature is 140°C, the sub-outer layer melting temperature is 150°C, and the middle layer melting temperature is 170°C.
[0042] Table 1 Amount of raw materials used in high-transparency polyethylene heat shrinkable film in Examples 1-7
[0043] Example 2: A highly transparent polyethylene heat shrinkable film, comprising an outer layer, a sub-outer layer, a middle layer, a sub-outer layer and an outer layer laminated in sequence with a thickness ratio of 1:2:6:2:1. The amount of raw materials used in each layer is shown in Table 1. The melt index (190°C, 2.16kg) of the outer layer No. I MLLDPE in Table 1 is 1.9g / 10min, and the density is 0.925g / cm 3 , selected from Japan Priman, model SP2520, the melt index (190℃, 2.16kg) of the MLLDPE layer II in the second outer layer and the inner layer is 1g / 10min, and the density is 0.9g / cm 3 , selected from Dow Chemical, USA, brand 5410G, the density of LDPE in the inner layer is 0.921g / cm 3 , melt index (190℃, 2.16kg) is 0.4g / 10min, selected from Singapore polyolefin F108-5, HDPE density is 0.949g / cm 3 The melt index (190°C, 2.16kg) is 0.82g / 10min, selected from Japan Primen, model 7000F.
[0044] The method for preparing the above-mentioned highly transparent polyethylene heat shrinkable film comprises the following steps: S1. According to the amounts in Table 1, No. I MLLDPE is used as the outer layer raw material, No. II MLLDPE is used as the secondary outer layer raw material, and LDPE, No. II MLLDPE and HDPE are mixed as the middle layer raw material; S2. The outer layer raw material, the sub-outer layer raw material and the middle layer raw material are melted, extruded and blown to obtain film bubbles, which are then pulled and corona treated to obtain a polyethylene heat shrinkable film. The blowing ratio is 1.2, the pulling ratio is 5, the outer layer melting temperature is 150°C, the sub-outer layer melting temperature is 180°C, and the middle layer melting temperature is 190°C.
[0045] Example 3-7: A highly transparent polyethylene heat shrinkable film, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0046] Example 8: A highly transparent polyethylene heat shrinkable film, which is different from Example 1 in that 5 kg of ultraviolet protective agent is also added to the outer layer, and the ultraviolet protective agent is prepared by Preparation Example 1. The ultraviolet protective agent is evenly mixed with No. 1 MLLDPE as the outer layer raw material.
[0047] Example 9: A highly transparent polyethylene heat shrinkable film, which is different from Example 1 in that 5 kg of ultraviolet protective agent is also added to the outer layer, and the ultraviolet protective agent is prepared by Preparation Example 2. The ultraviolet protective agent is evenly mixed with No. 1 MLLDPE as the outer layer raw material.
[0048] Example 10: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the UV protective agent is made from Preparation Example 3.
[0049] Example 11: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the UV protective agent is made from Preparation Example 4.
[0050] Example 12: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the UV protective agent is made from Preparation Example 5.
[0051] Example 13: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the UV protective agent is made from Preparation Example 6.
[0052] Example 14: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the UV protective agent is made from Preparation Example 7.
[0053] Example 15: A highly transparent polyethylene heat shrinkable film, which is different from Example 13 in that the UV protective agent is made from Preparation Example 8.
[0054] Example 16: A highly transparent polyethylene heat shrinkable film, which is different from Example 13 in that the UV protective agent is made from Preparation Example 9.
[0055] Example 17: A highly transparent polyethylene heat shrinkable film, which is different from Example 13 in that the UV protective agent is made from Preparation Example 10.
[0056] Example 18: A highly transparent polyethylene heat shrinkable film, which is different from Example 8 in that the ultraviolet protective agent is the ultraviolet absorber UV360.
[0057] Comparative Example
[0058] Comparative Example 1: A highly transparent polyethylene heat shrinkable film, which differs from Example 1 in that no outer layer is provided, and only includes a sub-outer layer, a middle layer and a sub-outer layer.
[0059] Comparative Example 2: A highly transparent polyethylene heat shrinkable film, which differs from Example 1 in that No. II MLLDPE is used to replace No. I MLLDPE in the outer layer.
[0060] Performance testing
[0061] The performance of the heat shrinkable films prepared in the examples and comparative examples was tested with reference to the following method, and the test results are recorded in Table 2.
[0062] 1. Tensile performance test: Test according to GB / T 1040.3-2006, tensile speed 200 mm / min.
[0063] 2. Puncture strength test: Test according to GB / T 37841-2019, puncture speed 200 mm / min.
[0064] 3. Transparency test: The transparency of the sample was tested using an ultraviolet-visible spectrophotometer (UV2600i, SHIMADZU, Japan) with a wavelength range of 800 nm.
[0065] The heat shrink film was placed under a 365nm UV lamp at 18.52W / m 2 After irradiation for 100 h, the tensile strength, puncture strength and transparency were tested again.
[0066] 4. Thickness: Test in accordance with GB / T6672-2001 "Mechanical measurement method for thickness of plastic film and sheet".
[0067] 5. External water contact angle: The static water contact angle was measured at room temperature using a contact angle tester (DCAT21, Germany). Each sample was tested at least 3 times with a water droplet of 5 μl.
[0068] Table 2 Performance test results of high-transparency polyethylene heat shrink film
[0069] It can be seen from the data in Examples 1-4 and Table 2 that by using specific amounts of LDPE, II MLLDPE and HDPE in the inner layer, the heat shrinkable films prepared in Examples 1-4 have higher transparency and good tensile and puncture resistance, but after ultraviolet irradiation, their strength and transparency decrease significantly.
[0070] Compared with Example 1, the mass ratio of the outer layer No. I MLLDPE, the sub-outer layer No. II MLLDPE and the middle layer MLLDPE in Example 5 is 2:2:1. It can be seen that it is similar to Example 1 and has good transparency and mechanical strength.
[0071] In Example 6, the mass ratio of the outer layer No. I MLLDPE, the sub-outer layer No. II MLLDPE and the middle layer MLLDPE is 3:3:1, and in Example 7, the mass ratio of the outer layer No. I MLLDPE, the sub-outer layer No. II MLLDPE and the middle layer MLLDPE is 1:1:1. Compared with Example 1, the mechanical strength of the heat shrinkable films prepared in Examples 6 and 7 decreases, and the transparency decreases.
[0072] Compared with Example 1, Example 8 and Example 9 further added the UV protective agent prepared in Preparation Example 1 and Preparation Example 2, respectively. The tensile strength, mechanical properties and transparency of the heat shrinkable films prepared in Example 8 and Example 9 were improved, and after ultraviolet irradiation, the decrease in tensile strength, puncture strength and transparency was reduced, the anti-ultraviolet ability was improved, and the hydrophobicity of the outer layer was improved.
[0073] Compared with Example 8, Example 10 uses the ultraviolet protection agent prepared in Preparation Example 3, wherein no silica sol is added. From the comparison of the data in Table 2, it can be seen that the tensile strength, puncture strength and transparency of the heat shrinkable film prepared in Example 10 are reduced, and after ultraviolet irradiation, the tensile strength, puncture strength and transparency decrease more than that in Example 8, indicating that the addition of silica sol can effectively improve the ultraviolet resistance and transparency of the heat shrinkable film.
[0074] In Example 11, the UV protective agent prepared in Preparation Example 4 was used, wherein silica sol and tannic acid were not added, and only epoxy resin emulsion was used to impregnate the cellulose film. It can be seen that the transparency of the heat shrinkable film prepared in Example 11 decreased, and the anti-ultraviolet ability decreased significantly, and the hydrophobicity decreased.
[0075] In Example 12, the UV protective agent prepared in Preparation Example 5 was used. Compared with Example 8, no epoxy resin emulsion was used for impregnation. It can be seen that the contact angle between the heat shrinkable film and water decreased, the hydrophobicity was weakened, and the tensile and puncture resistance were reduced, and the anti-UV ability was slightly reduced.
[0076] Compared with Example 8, Example 13 and Example 14 respectively use the ultraviolet protective agents prepared in Preparation Example 6 and Preparation Example 7. Table 2 shows that the transparency of the heat shrinkable films prepared in Example 13 and Example 14 is increased, and the tensile strength and puncture strength do not change much. However, after ultraviolet irradiation, the decrease in transparency, tensile strength and puncture strength is reduced, and the hydrophobicity is enhanced.
[0077] In Example 15, the ultraviolet protective agent prepared in Preparation Example 8 was used. Compared with Example 13, no water-soluble carbon quantum dots were added in Preparation Example 8. After ultraviolet irradiation, the tensile strength and puncture strength of the heat shrinkable film decreased more, and the transmittance decreased.
[0078] Compared with Example 13, Example 16 uses the UV protective agent prepared in Preparation Example 9. Compared with Preparation Example 6, no divinyltetramethyldisilazane is added. As shown in Table 2, the anti-UV ability does not change much, but the hydrophobicity and transparency are affected to a certain extent.
[0079] In Example 17, the UV protective agent prepared in Preparation Example 10 was used. Compared with Preparation Example 6, no polyvinyl alcohol aqueous solution was added. Table 2 shows that the transparency of the heat shrinkable film prepared in Example 17 decreased, and the puncture resistance and tensile strength were slightly weakened.
[0080] In Example 18, a commercially available ultraviolet absorber UV360 is used. Compared with Example 1, although it improves the ultraviolet aging resistance of the heat shrinkable film to a certain extent, it has little effect on the hydrophobicity and transparency of the heat shrinkable film.
[0081] In Comparative Example 1, no outer layer is provided, and only a sub-outer layer, a middle layer and a sub-outer layer are used. Compared with Example 1, the transparency of the heat shrinkable film is improved, but the tensile strength and the puncture strength are weakened.
[0082] In Comparative Example 2, No. II MLLDPE is used as the outer layer material. Compared with Example 1, the tensile strength and puncture strength are reduced, and the other properties do not change much.
[0083] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A highly transparent polyethylene heat shrinkable film, characterized in that: It includes an outer layer, a sub-outer layer, a middle layer, a sub-outer layer and an outer layer arranged in sequence; The outer layer includes No. I MLLDPE, the sub-outer layer includes No. II MLLDPE, and the inner layer includes LDPE, No. II MLLDPE and HDPE in a mass ratio of 1:1-1.4:1-1.2; The density of the No. 1 MLLDPE is 0.925-0.927 g / cm 3 , melt index is 1.3-1.5g / 10min; The density of the II MMLDPE is 0.9-0.92 g / cm 3 , the melt index is 0.5-1g / 10min.
2. The highly transparent polyethylene heat shrinkable film according to claim 1, characterized in that: The mass ratio of the outer layer No. I MLLDPE, the sub-outer layer No. II MLLDPE and the middle layer No. II MLLDPE is 2-2.5:2-2.5:
1.
3. The highly transparent polyethylene heat shrinkable film according to claim 1, characterized in that: 3-5 parts by weight of ultraviolet protection agent are also added to the outer layer.
4. The highly transparent polyethylene heat shrinkable film according to claim 3, characterized in that: The preparation method of the ultraviolet protection agent is as follows: The cellulose nanofibrils are placed in deionized water and ultrasonically dispersed for 1-2 hours to obtain a suspension with a concentration of 0.5-1 wt%, which is then filtered to obtain a cellulose membrane; The cellulose membrane is vacuum impregnated in a mixed solution containing modified nano-silica sol and tannic acid, and then dried at 45-50° C. for 10-12 hours to obtain a modified cellulose membrane, wherein the mass ratio of tannic acid to modified nano-silica sol is 0.7:15-16; The epoxy resin and the curing agent are mixed to prepare the epoxy resin emulsion, the modified cellulose film is immersed in the epoxy resin emulsion for 10-20 minutes, pressed at a pressure of 0.03-0.035 MPa until the epoxy resin is completely cured, and crushed to prepare the ultraviolet protective agent.
5. The highly transparent polyethylene heat shrinkable film according to claim 4, characterized in that: The modified nano-silica sol is prepared by the following method: dispersing nano-silica into a polyvinyl alcohol aqueous solution with a concentration of 8-10wt%, ultrasonicating for 20-30min, adding water-soluble carbon quantum dots and divinyltetramethyldisilazane, and mixing evenly to prepare the modified nano-silica sol, wherein the mass ratio of silicon dioxide, divinyltetramethyldisilazane and water-soluble carbon quantum dots is 1:0.6-0.9:0.2-0.
4.
6. The highly transparent polyethylene heat shrinkable film according to claim 4, characterized in that: The vacuum degree of the vacuum impregnation is 0.05-0.08 MPa, and the impregnation time is 40-60 min.
7. The highly transparent polyethylene heat shrinkable film according to claim 1, characterized in that: The thickness ratio of the outer layer, the sub-outer layer, the middle layer, the sub-outer layer and the outer layer is 1:2-3:6:2-3:
1.
8. The highly transparent polyethylene heat shrinkable film according to claim 1, characterized in that: In the middle layer, the density of LDPE is 0.921-0.922 g / cm 3 The melt index is 0.33-0.4 g / 10 min, and the density of the HDPE is 0.949-0.961 g / cm 3 , the melt index is 0.7-0.82g / 10min.
9. The method for preparing the highly transparent polyethylene heat shrinkable film according to any one of claims 1 to 8, characterized in that: The following steps are involved: No. I MLLDPE is used as the outer layer material, No. II MLLDPE is used as the secondary outer layer material, and LDPE, No. II MLLDPE and HDPE are mixed as the middle layer material; The outer layer raw material, the sub-outer layer raw material and the middle layer raw material are melted, extruded and inflated to obtain film bubbles, which are then pulled and corona-treated to obtain a polyethylene heat shrinkable film.
10. The method for preparing a highly transparent polyethylene heat shrinkable film according to claim 9, characterized in that: The blowing ratio is 1.2-3, the drawing ratio is 5-7, the melting temperature of the outer layer is 140-150°C, the melting temperature of the second outer layer is 150-180°C, and the melting temperature of the middle layer is 170-190°C.
Citation Information
Patent Citations
Five-layer polyethylene repackaging hot shrinkable film and preparation method thereof
CN104354427A
High-transparency high-strength polyethylene heat shrink film and preparation method thereof
CN115923289A
High-transparency polyethylene heat shrink film and preparation method thereof
CN116728930A